An Introduction to European Foreign Policy - CAMERON, Flaser (Routledge, 2007)
This text is the best introduction to the history, institutions, actors, processes and challenges of European Foreign Policy. This 2nd edition has been fully revised and updated to reflect the substantial changes to European Foreign Policy as a result of the Lisbon Treaty and other significant changes in European and global politics.